Workload and Work Stress on Nurses’ Transfer Intention: Mediating Role of Burnout - Amazia Aurora Kusuma; Survival Survival; Lembah Andriani (Information Technology and Science (ITScience), 2026)
This study examines the effects of workload and work stress on nurses’ turnover intention, with burnout as a mediating variable, at Indriati Hospital, Boyolali. A quantitative causal design was applied using data collected through structured questionnaires from 65 contract nurses. Inferential statistical analysis was employed to evaluate both direct and indirect relationships among the variables. The results indicate that workload has a significant direct effect on turnover intention, implying that higher workload levels increase nurses’ intentions to leave their jobs. In contrast, work stress does not directly influence turnover intention but has a significant positive effect on burnout. Burnout, in turn, significantly affects turnover intention and mediates the relationship between work stress and turnover intention, confirming its role as a key psychological mechanism in nurse retention. Conversely, workload does not significantly influence burnout and therefore does not mediate its relationship with turnover intention, suggesting that workload operates through a direct pathway. These findings highlight the importance of organizational strategies focused on stress management, burnout prevention, and effective workload allocation to reduce turnover intention among nurses. Future research is recommended to involve broader samples and additional organizational factors to strengthen the generalizability of the findings in healthcare contexts.